Mixed convection flow of a nanofluid in a lid-driven cavity with a wavy wall - Abu-Nada, Eiyad; Chamkha, Ali J. (International communications in heat and mass transfer, 2014)
This work is focused on the numerical modeling of steady laminar mixed convection flow in a lid-driven cavity with a wavy wall filled with a water–CuO nanofluid. The left and right walls of the enclosure are kept insulated while the bottom and top walls are maintained at constant temperatures with the top surface being the heated lid wall and moving at a constant speed. The governing equations for this investigation are given in terms of the stream function–vorticity formulation and are non-dimensionalized and then solved numerically subject to appropriate boundary conditions by a second-order accurate finite-volume method. Various comparisons with previously published work are performed and the results are found to be in good agreement. A parametric study of the governing parameters such as the Richardson number, bottom wall geometry ratio (B/H) and the nanoparticles volume fraction is conducted and a representative set of graphical results is presented and discussed to illustrate the effects of these parameters on the flow and heat transfer characteristics. It is found that the presence of nanoparticles causes significant heat transfer augmentation for all values of Richardson numbers and bottom wall geometry ratios.